Calpain-2/p35-p25/Cdk5 pathway is involved in the neuronal apoptosis induced by polybrominated diphenyl ether-153. (5th August 2017) - Zhang, Hongmei; Chang, Lijun; Zhang, Huajun; Nie, Jisheng; Zhang, Zhihong; Yang, Xiaorong; Vuong, Ann M.; Wang, Zemin; Chen, Aimin; Niu, Qiao
Graphical abstract: Highlights: BDE-153 can induce cell apoptosis in rat's hippocampus and primary neurons. Calpain-2/p35-p25/Cdk5 pathway is involved in the neuronal apoptosis induced by BDE-153. Inhibition of calpain or p25/Cdk5 activity can rescue the neuronal apoptosis. Abstract: Polybrominated diphenyl ethers (PBDEs) have been demonstrated to induce neurotoxicity in experimental rats and mice, with neuronal apoptosis as one of the major mechanisms, however, the mechanisms underlying PBDEs-induced neuronal apoptosis remain unclear. In this study, we aimed to investigate the role of calpain/p35-p25/Cdk5 pathway in BDE-153-induced neuronal apoptosis in the hippocampus and primary neurons in rats. Results showed that compared to the controls, neuronal apoptosis was significantly increased in vivo and ex vivo, as manifested by the increased hippocampus TUNEL-positive cell rates, apoptotic neurons in Hoechst and AO/EB staining, and the increased LDH activity and percentage of Annexin V-positive cells in rat hippocampus and primary neurons. Calpain activity was significantly increased in all the BDE-153-treated groups in vivo and ex vivo when compared to non-treatment controls. In addition, we showed that calpain-2 accounted for the calpain activation instead of calpain-1, as demonstrated by the up-regulated mRNA and protein expressions in calpain-2 but not calpain-1. Activated calpain truncated p35 into p25, which resulted in the p25/Cdk5 formation and activation. Calpain inhibitor PD150606 or p25/Cdk5 inhibitor Roscovitine relieved neuronal apoptosis mainly via inhibiting the p25/Cdk5 activation. Overall, the findings suggested that calpain-2/p35-p25/Cdk5 pathway was involved in BDE-153-induced neuronal apoptosis, which provides novel insight into the mechanisms of PBDE neurotoxicity.